Learning Styles: Preferred Learning Choices and Behaviors of Saudi Male and Female EFL Learners (Journal of Education and Educational Development, 2020)
Learning styles are the differences in personal characteristics, strengths and preferences, describing how individuals acquire, process and store information. Learners approach information differently from each other due to their different instincts and natural dispositions. In the pretext of learning styles what is being taught has least importance than how’s being taught as in current scenario, teachers adapt their teaching techniques according to the learners preferred learning styles. Based on the review of previous context(s), the present study aims at investigating the learning style preferences of 200 Saudi male and female EFL learners at Taif University. For this purpose, a questionnaire was developed with closed ended questions by employing Likert’s five point scale to collect the data from 100 male and 100 female Saudi EFL learners that represents quantitative dimension of the work. The study probed into how different learners took in information by using their senses, intellect, force and physical movements. Furthermore, the research investigated what special measures teachers should take during teaching to develop the learners’ awareness about their dominant learning styles coupled with designing the strategies to promote learning according to their unique dispositions. The findings manifest significant differences in the learning style of Taif University’s male and female EFL learners because of the learners’ physical and biological differences as well as their diverse social and cultural norms.